La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Centre de recherche interuniversitaire sur la littérature et la culture au Québec [CRILCQ], 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Naviguer les attentes genrées de la communauté de danse swing de Montréal - Batty, Megan (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Gender and Extreme Metal: Understanding Gender Relations in the Montreal Extreme Metal Scene With Schippers' Gender Framework - Beauchamp, Caroline (Université Concordia, 2021)
Extreme metal is a masculine space, yet more and more women join in. They face a contradiction: as women, they are expected to adopt feminine behaviours; however, they are part of a subculture that valorizes warrior masculinity. I sought to understand the gender expectations of the Montreal extreme metal scene and interpret the contradictions encountered by women in this scene with the help of Schippers’ (2007) theoretical framework on gender. To do so, I conducted 16 individual interviews with women and men who take part in the scene. This research fills a gap in the literature on gender that derives from Connell and Schippers’ writings and addresses issues that the field of metal studies has brushed over. I found that metal men are the “default” participants in the scene. They are expected to be fine music connoisseurs and even become musicians. In contrast, women’s presence is heterosexualized and attributed to a romantic or sexual interest in metal men. Women are suspected of being “poseuses” or groupies with no real interest in the music until proven otherwise. To become legitimate participants, they have to overcome those expectations and prove that they are worthy of being viewed through the prism of masculinity rather than femininity. They do so by proving their exceptionality through manhood acts and distancing themselves from other women. Despite their gender transgressions, women’s presence does not fundamentally question gender relations but reaffirms the overall primacy of masculinity over femininity.

Énonciation, sexualités et genre en musique chez Philémon Cimon, Pierre Lapointe et Ariane Moffatt - Konaté, Khady (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Dans ce texte est proposée une « lecture du genre » (Boisclair 2002) des oeuvres de Philémon Cimon (L’été, Les femmes comme des montagnes), Pierre Lapointe (Pierre Lapointe, Sentiments humains) et Ariane Moffatt (Aquanaute, Le coeur dans la tête, Tous les sens). L’étude des chansons contenues sur ces albums prend pour point de départ une interrogation des subjectivités genrées de ces trois artistes, entre personne réelle et persona, et montre que ces dernières façonnent leurs compositions. La sollicitation du concept de sexe/genre ouvre dès lors la porte à l’exploration des représentations des identités sexuelles et de genre dans ces chansons, où les identités des artistes se trouvent mises en abîme. En s’intéressant à l’énonciation et au discours (en particulier, au discours amoureux) contenu dans le texte des chansons sélectionnées, il est possible de rendre compte de la reproduction des injonctions à l’hétérosexualité et des poncifs qui cloisonnent le genre, ainsi que des glissements et brouillages qui autorisent des resignifications du genre. Ainsi, chez Cimon, on observe la reconduite du point de vue masculin où la valeur du féminin réside dans sa capacité à émerveiller le sujet et à susciter son désir. À l’opposé, les textes de Lapointe et Moffatt dépeignent des personnages et des récits queer, bien que leur identité queer n’ait pas été revendiquée à l’heure de la parution de leurs oeuvres.

Genre, rap et enjeux de la visibilité dans l'espace public des rappeuses à Montréal : de la gestion de l'apparence physique pour être reconnue en tant qu'artiste - Lesacher, Claire (Les Cahiers de la Société québécoise de recherche en musique, 2021)

The Double Bind That Is Not a Bond: Cohen and Women - Pally, Marcia (From This Broken Hill I Sing to You: God, Sex, and Politics in the Work of Leonard Cohen, 2021)
Leonard Cohen's troubled relationship with God is here mapped onto his troubled relationships with sex and politics. Analysing Covenantal theology and its place in Cohen's work, this book is the first to trace a consistent theology across sixty years of Cohen's writing, drawing on his Jewish heritage and its expression in his lyrics and poems.Cohen's commitment to covenant, and his anger at this God who made us so prone to failing it, undergird the faith, frustration, and sardonic taunting of Cohen's work. Both his faith and ire are traced through: · Cohen's unorthodox use of Jewish and Christian imagery · His writings about women, politics, and the Holocaust · His final theology, You Want It Darker, released three weeks before his death.
Keywords: Music / General; Religion / Judaism / Theology; Religion / Theology

Gender and Embodiment in the Contemporary Montreal Swing Dance Community - Batty, Megan (Université McGill, 2020)
"This thesis explores embodiment and gender within the contemporary Montreal swing dance community. Drawing on scholarship in musicology, dance studies, jazz studies, and gender studies, I investigate the relationship between dancers and musicians/DJs. I explore the many facets of this choreomusical conversation and trace this dialogic and collaborative relationship on the social dance floor. The contemporary community is a product of the swing revival and navigating issues of authenticity thus becomes an important consideration for dancers, musicians, and DJs alike. One product of this revival is the set of heteronormative values that underpin the contemporary community. I investigate to what extent these values are reified, challenged, or altogether subverted by participants through musical and choreomusical choices. To this end I conducted interviews with six informants, each of whom has experience as both a dancer and musician and/or DJ. Their privileged position arising from their dual experience affords them insight on the ways in which dancers and musicians/DJs function within the community. This thesis builds on existing scholarship by situating the voices of individuals with choreomusical experience in dialogue with existing scholarship, and ultimately revalues the importance of both embodied knowledge and gender within the swing community"– Author's abstract

Représentations du féminin et énonciation lyrique dans la chanson québécoise contemporaine : perspectives sur le sexe/genre chez Ariane Moffatt, Pierre Lapointe et Philémon Cimon - Konaté, Khady (Université d'Ottawa, 2020)
Cette thèse se propose de faire une analyse du discours sur les représentations du féminin et les implications du sexe/genre dans la chanson québécoise contemporaine, à travers les œuvres et la persona de trois auteur·ice·s-compositeur·ice·s-interprètes (ACI): Ariane Moffatt, Pierre Lapointe et Philémon Cimon. Notre analyse part d’abord du constat que les chansons de Moffatt, Lapointe et Cimon figurent des sujets lyriques, dont la parole et le geste sont modulés par les enjeux énonciatifs que posent le lyrisme. Pour rendre compte de la spécificité de la chanson comme pratique poétique réunissant paroles, musique et interprétation, nous proposons de faire une étude sémantique des chansons pour chacun·e des ACI, en nous attardant dans un premier temps aux questions soulevées par le lyrisme, puis en faisant la somme des aspects relevant du sexe/genre présents dans leurs univers sonores respectifs avec le renfort de la théorie féministe et des études de genre, d’après une perspective postmoderne. Notre lecture cherche à souligner les reconduites et les poncifs liés au féminin, mais également à saisir les propositions et les configurations qui s’écartent des lieux communs, tant pour les modèles féminins valorisés que pour les modèles amoureux et les rapports sociaux de sexe et de genre suggérés par les chansons. La comparaison entre les chansons des trois artistes permet ainsi de dégager des points de convergence, tout en révélant les particularités de leurs œuvres.

Imaginary Women, Imaginary Audience: Gender and Top 40 Radio in Montréal - Maki, Christine (Women in Radio: Unfiltered Voices from Canada, 2020)
Though they no longer call themselves Top 40, popular music radio stations remain present on the dial today, complete with loud, mostly male DJs, hoping to attract a mainly female audi ence. Using the talk on two Montréal music stations, which hire mainly male announcers who select music assumed to fit wom en’s tastes, Christine Maki examines the continuing perception that women’s voices aren’t low or authoritative enough and that emotional issues prevent them from presenting difficult news stories. Her conclusion: the overall medium remains relatively unchanged over the decades, despite massive evolution in the wider media landscape.

Shekhinah in the Music Videos of Leonard Cohen - Měsíc, Jiří (From Page to Screen: Modification and Misrepresentation of Female Characters in Audiovisual Media, 2020)